Learning to be you: transitional identity of British soldiers leaving the armed services - Flint, Kevin James (2013)
In the field of social science, it is commonly acknowledged that we are what we do. 'Learning to be you' is a qualitative, longitudinal study, which examines career transitions from the British Army to civilian life. This study is not about the success or failure of any particular feature of the administrative process. It is concerned with people's identity, and by focussing on identity, certain successes and failures of the journey become visible. This study is multifaceted, just as identity is complicated and heterogeneous. Consequently, I have sought to develop a collaborative academic framework, combining the psychoanalytical theories of Freud, the discourse paradigms of Foucault, the structuralist perspectives of Bourdieu and the performed identities of Goffman. I envisage gliding surfaces of identity and I use the four theorists to account for these interrelating planes. Two main questions are addressed. How do transitions from the British Army to civilian life impact on identity? How does an institutionalised identity, positioned by rank and structure have to adapt to civilian career transitions? The findings illustrate a learning to cope via adaptation that is simultaneously frightening yet also emancipating. Even in successful transitions, there is disturbance and largely these prominent upheavals at the point of service departure have become normalised' within the military community. The key conclusions made by my study are: • Ex- service personnel have to adjust and modify their identity to fit to the new civilian environment. The adjustment can be painful, emancipating and it can be sudden to the individual. • Stress and risk at the point of service departure has been normalised. • Greater visibility of the civilian world is essential in order to make the best career choices. • Some military jobs have greater transferability than others do. • A predictability matrix may provide practitioners and service leavers with a helpful assessment of the resettlement spectrum. • Indications point toward an increasing need to consider wider post-discharge resettlement provision. • Further longitudinal resettlement research is required with the findings made available to key practitioners.